Peran Subbagian Keuangan dan Aset dalam Mendukung Layanan Pendidikan di Lingkungan Dinas Pendidikan Provinsi Kalimantan Tengah - Yuliana Agustin; Syahmidi Syahmidi (International Forum of Researchers and Lecturers, 2025)
Quality education services are closely linked to the effectiveness of financial and asset governance within local government institutions. This study aims to explore in depth the strategic role of the Finance and Assets Subdivision in enhancing the effectiveness of education services under the Central Kalimantan Provincial Education Office. Using a descriptive qualitative approach, data were collected through interviews, observation, and documentation. The analysis was carried out following the Miles and Huberman model, which involves data reduction, data display, and conclusion drawing. The results indicate that the Finance Subdivision plays a critical role in needs-based budget planning, ensuring that financial allocations align with educational priorities and policies. It manages key funding sources such as School Operational Assistance (BOS) and Special Allocation Funds (DAK) with a focus on transparency, accountability, and timely reporting. Meanwhile, the Asset Subdivision contributes through systematic recording, equitable distribution, and optimal utilization of regional property. These responsibilities are supported by regular training programs and consistent monitoring to ensure that facilities remain functional and beneficial for educational purposes. The implementation of integrated digital management systems, such as SIMDA, SIKD, and SIPKD, has significantly improved data accuracy, accessibility, and overall management efficiency. These systems allow for more transparent governance and facilitate informed decision-making at the institutional level. The study concludes that the active and coordinated role of the Finance and Assets Subdivision forms a strong foundation for professional, efficient, and sustainable education governance. The findings suggest that strengthening human resource capacity, enhancing interdepartmental coordination, and further integrating digital information systems are essential strategies to improve the quality and equity of education services in the region. Such improvements will contribute to achieving better educational outcomes and fostering public trust in government-managed education services.